When night comes - Hirschi, Ron.; Mangelsen, Thomas D. (Honesdale, Pa. : Caroline House, 2000)
A look at the night life of various wild animals.
Booklist.
School Library Journal.
2.9
K-3
Keywords: Animals -- Juvenile literature; Nocturnal animals -- Juvenile literature; Animals; Nocturnal animals; Animals; Nocturnal animals